Elementos de análise combinatória no ensino fundamental : uma abordagem com mágicas e resolução de problemas - Bassan, Débora Regina (Universidade Federal de São Carlos, 2016)
This work AIMS to Develop the content of combinatorial analysis in the class of 6th and 7th grade of elementary school II in a school in the state of São Paulo. For this, there was the use of contextualized activities using leaves, activities and resources Involving magic, aiming to arouse curiosity and interest in learning Combinatorial through problem solving. The theme was chosen because of the difficulty of students in solving counting problems and is being explored little in basic education, although it appears in documents oficiais- National Curriculum Parameters and Curriculum of the State of São Paulo. We opted for the mathematical magic feature to make more meaningful and enjoyable learning Combinatorics, seeking the motivation of students to Actively Participate in class, joining the pleasure the act of learning. During the performance of activities, it was Noted que the students felt motivated, Relating the content of combinatorial analysis with a fun practice by magic. They Showed great enthusiasm in carrying out the activities, Especially in the days que had the magic. The didactic proposal with the use of leaf-activities Reached most of the students, who Were Involved and were very active During class, Resulting in collegues learning Combinatorial Analysis content. All activities Reached The proposed objectives, validating the Proposed teacher. After the completion of the activities, students felt more confident to expose Their reasoning, presenting solving strategies and explore the problem in search of a suitable solution.
Keywords: Mágica matemática; Ensino de combinatória; Problemas de contagem; Combinatorial teaching; Math magic; Counting problems; CIENCIAS EXATAS E DA TERRA